Facile green strategy for improving thermoelectric performance of carbon nanotube/polyaniline composites by ethanol treatment. (22nd March 2020) - Li, Pengcheng; Zhao, Yuhui; Li, Hui; Liu, Siqi; Liang, Yuan; Cheng, Xiaolong; He, Chaobin
Abstract: In contrast to commonly adopted harmful reagents which are not favorable for human body and environment, a facile environmental friendly dedoping approach is proposed to modulate carrier transport and thermoelectric properties of single-walled carbon nanotube (SWCNT)/polyaniline (PANI) composites by ethanol treatment. Compared with the pristine composite films, PANI is partially dedoped after treatments, which results in typically increasing of Seebeck coefficient and deteriorative electrical conductivity. As the interconnected conductive CNT networks provide extra pathways to facilitate carrier transport, the electrical conductivity is only slightly decreased. Consequently, an enhanced power factor of 362 μW m −1 K −2 is achieved, which is superior to the pristine composite of 234 μW m −1 K −2 . Furthermore, the flexible thermoelectric device based on the treated composites generates high output power of 2.86 μW and high power density of 745 μW cm −2 at ΔT = 50 K. With the advantages of low cost, facile processing, and environmental friendly, this strategy exhibits potential application for commercial thermoelectric conversion. Graphical abstract: Image 1 Highlights: Thermoelectric performance of SWCNT/PANI composite is improved by ethanol soaking. Partial dedoping of polyaniline modulates carrier transport. Seebeck coefficient is greatly increased with slightly decreased conductivity. High power factor of 362 μW m −1 K −2 is achieved after ethanol treatment.